InSAR-derived surface deformation and numerical simulation: constraints on the seismogenic fault and rupture process of the 2021 MS 5.4 Baicheng earthquake - Hanxiao Deng; Zhenyun Wu; Keyi Mao; Yuan Yao; Fengnian Chang; Shaochun Dong; Changsheng Li; Fei Xia; Hongwei Yin (Geomorphology, 2026)

Spatiotemporal Characteristics and Driving Mechanisms of Non‐Extreme Precipitation Variability Over Mainland China - Yue Sun; Baofu Li; Keyi Tong; Dong Cui; Kairong Shi; Haijun Liu (International Journal of Climatology, 2026)
Against the background of global warming, non‐extreme precipitation is an important component of the regional moisture background and the normal hydrological cycle, yet its variability remains insufficiently understood. Based on daily CHM_PRE V2 precipitation for 1961–2024, ERA5 reanalysis, and outputs from 14 CMIP6 models, this study systematically investigates the spatiotemporal characteristics of non‐extreme precipitation variability over mainland China, its projected responses under 1.5°C and 2.0°C global warming levels, and its driving mechanisms. The results show that non‐extreme precipitation variability exhibits pronounced regional contrasts and strong timescale dependence, with the eastern monsoon region showing the largest variability, the arid northwest and the Tibetan Plateau exhibiting lower variability, and the intraseasonal scale displaying the strongest response. Under future warming, non‐extreme precipitation variability generally increases, but with marked regional differences: it decreases in the eastern monsoon region but increases in northwestern China and over the Tibetan Plateau, and the magnitude of change is larger at 2.0°C than at 1.5°C. A thermodynamic–dynamic decomposition of projected 850‐hPa moisture flux convergence under the 1.5°C warming level further shows that the regional mechanisms are highly heterogeneous: dynamic circulation adjustment dominates the moisture flux convergence (MFC) response in the eastern monsoon region and the arid northwest, whereas thermodynamic moistening dominates over the Tibetan Plateau. Thermodynamic background factors exert some influence, but their explanatory power is limited. In contrast, large‐scale circulation exerts clearer seasonal and regional controls. In particular, summer non‐extreme precipitation variability in eastern China is closely linked to the western Pacific subtropical high, and the associated enhancement of low‐level MFC is primarily dominated by anomalous circulation rather than by the direct thermodynamic contribution of increased specific humidity. Overall, non‐extreme precipitation variability over mainland China arises from the combined effects of regional thermodynamic background differences and seasonal reorganisation of large‐scale circulation.

Coupling upconversion effect with p-n heterojunction on TiAl6V4 to eradicate bacterial biofilms - Keyi Yao; Lixuan Huang; Jie Shao; Junyu Dong; Junhua Xu; Yongsheng Liu; Sze Wing Cheung; Lin Xiang; Xuemei Zhou (Chemical Engineering Journal, 2026)

Reinforcing the high-rate cycling stability of LiNi0.9Mn0.1O2 cathode by a component-induced structure-microstructure regulation strategy - Keyi Xian; Huanming Zhuo; Xuelong Rao; Yuehuan Peng; Xiangrui Xu; Yanfei Wang; Dong Wang; Chunhui Wang; Xing Ou (Chemical Engineering Journal, 2026)

A plasticity-aware machine learning framework for genomic prediction and resource-efficient wheat breeding under multi-environment conditions - Lei Li; Cong Zhao; Huihui Li; Xi Tian; Jindong Liu; Duoxia Wang; Keyi Wang; Shuaipeng Fei; Guoliang Wan; Jianqi Zeng; Yachao Dong; Jixin Li; et al. (Computers and Electronics in Agriculture, 2026)

A high-performance aqueous redox flow battery with long cyclic stability enabled by a novel Janus membrane self-assembled from polyelectrolytes - Quanhu Sun; Keyi Dong; Zefeng Yan; Tian Lv; Yan Tan; Jiaxin Yang; Yu Wang; Weiyang Tang; Tao Chen (Chemical Engineering Journal, 2025)

Application of deep learning for multi-scale behavioral analysis in SNCA E46K Parkinson’s disease drosophila - Keyi Dong; April Burch; Kang Huang (Cognitive Neurodynamics, 2025)

Local neighbor Normalization: Reconciling accurate normalization and heterogeneity recovery in large-scale metabolomics - Keyi Lu; Yaru Liu; Kian-Kai Cheng; Fanjing Guo; Lingli Deng; Jiyang Dong (Analytica Chimica Acta, 2025)

Reconstruction of cobalt atoms in ZIF-67 and in-situ growth of carbon nanotubes at low temperature for High-Performance strain sensors - Xiao Li; Tian Lv; Keyi Dong; Jiaxin Yang; Weiyang Tang; Zilin Chen; Yu Duan; Quanhu Sun; Dongmei Zhai; Tao Chen (Chemical Engineering Journal, 2025)

A microphase-separation ionogel electrolyte for highly stretchable all-solid-state supercapacitors - Weiyang Tang; Keyi Dong; Zilin Chen; Yu Duan; Quanhu Sun; Xiao Li; Dongmei Zhai; Tian Lv; Tao Chen (Chemical Engineering Journal, 2024)

Rational design of bilayer heterogeneous poly(ionic liquid)s electrolytes for high-performance flexible supercapacitors with ultraslow self-discharge rate - Keyi Dong; Weiyang Tang; Quanhu Sun; Zilin Chen; Xiao Li; Dongmei Zhai; Zefeng Yan; Jiaxin Yang; Tian Lv; Tao Chen (Chemical Engineering Journal, 2024)

Constructing bilayer heterogeneous organogel electrolytes of Lewis acidic/basic polymers to suppress self-discharge of supercapacitors - Yanan Liu; Keyi Dong; Tian Lv; Zilin Chen; Shaokui Cao; Feng Zheng; Tao Chen (Chemical Engineering Journal, 2024)

A novel hydrogel electrolyte for all-climate high-performance flexible zinc-ion hybrid capacitors within temperature range from −50 to 100 °C - Yu Duan; Tian Lv; Keyi Dong; Feng Zheng; Xiao Li; Yunlong Qi; Zilin Chen; Weiyang Tang; Quanhu Sun; Shaokui Cao; Tao Chen (Chemical Engineering Journal, 2023)

Nanoplastics induce molecular toxicity in earthworm: Integrated multi-omics, morphological, and intestinal microorganism analyses - Ronggui Tang; Dong Zhu; Yongming Luo; Defu He; Haibo Zhang; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Keyi Chen; Yan Yan; Xinghang Lu; Minshen Ying; Tao Sun; et al. (Journal of Hazardous Materials, 2023)

Easy regulation of chitosan-based hydrogel microstructure with citric acid as an efficient buffer - Keyi Li; Xueting Yang; Xin Dong; Hongyan Cao; Shujuan Zhuang; Xiangling Gu (Carbohydrate Polymers, 2023)